Blood and intra-abdominal Candida spp. from a multicentre study conducted in Madrid using EUCAST: emergence of fluconazole resistance in Candida parapsilosis, low echinocandin resistance and absence of Candida auris. (29th August 2022) - Díaz-García, Judith; Gómez, Ana; Machado, Marina; Alcalá, Luis; Reigadas, Elena; Sánchez-Carrillo, Carlos; Pérez-Ayala, Ana; Gómez-García De La Pedrosa, Elia; González-Romo, Fernando; Cuétara, María Soledad; García-Esteban, Coral; Quiles-Melero, Inmaculada; et al.
Abstract: Objectives: We prospectively monitored the epidemiology and antifungal susceptibility of Candida spp. from blood cultures and intra-abdominal samples in patients admitted to hospitals in the Madrid area. Methods: Between 2019 and 2021, we prospectively collected incident isolates [one per species, patient and compartment (blood cultures versus intra-abdominal samples)] from patients admitted to any of 16 hospitals located in Madrid. We studied the antifungal susceptibilities to amphotericin B, triazoles, micafungin, anidulafungin and ibrexafungerp following the EUCAST E.Def 7.3.2 procedure. Results: A total of 2107 Candida spp. isolates (1895 patients) from blood cultures (51.7%) and intra-abdominal samples were collected. Candida albicans, the Candida glabrata complex, the Candida parapsilosis complex, Candida tropicalis and Candida krusei accounted for 96.9% of the isolates; in contrast, Candida auris was undetected. Fluconazole resistance in Candida spp. was higher in blood cultures than in intra-abdominal samples (9.1% versus 8.2%; P > 0.05), especially for the C. parapsilosis complex (16.6% versus 3.6%, P < 0.05), whereas echinocandin resistance tended to be lower in blood cultures (0.5% versus 1.0%; P > 0.05). Resistance rates have risen, particularly for fluconazole in blood culture isolates, which increased sharply in 2021. Ibrexafungerp showed in vitro activity against most isolates. Species distributions and resistance rates varied among hospitals. Conclusions: Whereas no C. auris isolates were detected, fluconazole-resistant C. parapsilosis isolates have been spreading across the region and this has pulled up the rate of fluconazole resistance. In contrast, the rate of echinocandin resistance continues to be low.